The Effect of 12 Weeks of Wrestling+ Specific Warm-Up Program on Dynamic Balance in Cadet Wrestlers - Rasoul Bayati; Ali Shamsi Majelan; Bahman Mirzaei (Biyumikānīk-i varzishī)
Objective: The aim of the present study was to investigate the effects of a 12 week Wrestling+ specific warm-up program on dynamic balance in cadet wrestlers. Methods: The study population included all cadet wrestlers in the city of Rasht from among whom 24 freestyle wrestlers were selected by the convenience sampling and divided into intervention and control groups. The Intervention group performed a Wrestling+ warm-up program for 12 weeks, three times a week and the control group performed routine warm-up during the same period. Y balance test was used for the assessment of dynamic balance in pre and post phases of the program. Independent samples t test, Dependent samples t test, and p-test were used for data analyses with preset alpha value of p<0.05. Results: The results indicated that there was a significant increase in reach distance of Y balance test and a significant decrease in the number of wrestlers at high risk in intervention group after implementation of 12 weeks wrestling+ warm-up program (p<0/05). However, there was no significant difference in any of the variables in the control group (p≥0/05). Conclusion: It seems that the wrestling+ warm-up program can improve the dynamic balance. Therefore, it is recommended that wrestlers and coaches use this new warm-up program before the specific training.